Prohibition of Marriages within the Same Clan in Batak Toba Samosir Customs from the Perspective of Islamic Law - Wardana, Wisnu; Sukiati, Sukiati; Zahara, Fatimah (Electronic Journal of Education, Social Economics and Technology, 2024)
Regulations regarding mahram and the prohibition of intermarriage in Samosir Batak society are one of the important aspects that influence social life and marriage. The clan in the Samosir Batak tradition has a very central position, so the prohibition on intermarriage within the clan is regulated to maintain the purity of the lineage and social harmony. In Islamic law, the prohibition on intermarriage can be analogous to the prohibition against mahram, namely people who are forbidden to marry because of blood or marriage relations. This research aims to examine the relationship between mahram in Islamic law and the prohibition on intermarriage in Samosir Batak custom, as well as exploring the similarities and differences between the two. The method used is descriptive qualitative with a normative approach. The research results show that there are similar goals between the two systems in protecting offspring and family honor. However, there are differences in determining which parties are considered mahram and semarga. This research suggests that there should be a deeper understanding of these two systems in order to create a balance between religious and customary law in Samosir Batak society. Even though there are differences in determining who is considered a mahram in Islamic law and who is considered a clan in Samosir Batak custom, these two systems have the same goals in maintaining family honor, protecting legitimate descendants, and preventing marriage within a close lineage. Socialization and Education requires more intensive outreach efforts regarding the differences and similarities between mahram in Islamic law and the prohibition on intermarriage in Samosir Batak custom. This is important to provide a clear understanding to the community, especially the younger generation, so that they can live their religious and traditional lives in harmony.